Porìvnânnââk stilìstičnij element novelìstiki V. Stefanika - Čornenʹkij, Âroslav (Stylistyka, 1998)
Artistic comparisons in V.Stephanik’s novel are considered as stylistic elements ofliterary production language, which consolidates contrasts, that are interdepended in the frames of one structure and represented world outlook and world sensation of author so as characters. In the base oftropes are the form and maintenance, which going in the structure ofthe text express the story, intensify the language of dramatis personae and than, representing their psychic state, form picturesque portrat characteristics, draw the nature pictures. Novels tropic promotes to comprehension of psychologism and figurativeness of V.Stephanik’s individual author’s style.